WORK ENGAGEMENT AS MEDIATOR OF COMPETENCE AND SELF-EFFICACY OF SERVICE QUALITY - Veimina Surya; Wahyuni Dian Purwati; Rian Adi Pamungkas (Kesatuan Press, 2023)
This study aimed to obtain empirical evidence of the effect of competence and self-efficacy on service quality with work engagement as an intervening variable using a cross-sectional study design and 100 health workers with civil servant status as respondents. The study's results prove that simultaneously and partially, competence and self-efficacy have a positive and significant direct effect on work engagement and service quality, and work engagement has a positive and significant effect on service quality. So work engagement positively mediates the relationship between competence and self-efficacy in improving the service quality. The partisanship of health workers by involving themselves will make competence and management efforts in developing self-efficacy more effective in improving the ability of health workers to deliver quality services to inpatients. Competence will enable health workers to improve the quality of services more optimally if they appreciate interprofessional input and fully practice their knowledge. The importance of generalizations that management must develop for health workers in giving trust and experience will be an impetus for health workers to provide quality services in inpatient installations.